2013
DOI: 10.1002/hyp.9813
|View full text |Cite
|
Sign up to set email alerts
|

The rivers of Africa: witness of climate change and human impact on the environment

Abstract: In this paper, we study the impact of climate change on river regimes in several parts of Africa, and we look at the most probable causes of these changes either climatically or anthropogenically driven. We study time series of updated monthly and annual runoff of rivers of North Africa, West Africa (Sahelian and humid tropical regions) and Central Africa, including the largest river basins: Niger and Volta rivers in West Africa, and Congo and Ogooue rivers in Central Africa. The recent years are studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 45 publications
6
110
1
3
Order By: Relevance
“…This hydrological paradox is strictly Sahelian [2,6,7,9,26,45,46,51]. Paturel et al [52] and Amani and Paturel [53] pointed out the necessary changes to be processed in hydrological regional norms in order to supply engineers with actual figures of rainfall and runoff characteristics, and new methods, able to account for the non-stationarity in hydrological variables.…”
Section: A Marked Increase In Runoff Coefficients and Discharges Of Smentioning
confidence: 99%
See 3 more Smart Citations
“…This hydrological paradox is strictly Sahelian [2,6,7,9,26,45,46,51]. Paturel et al [52] and Amani and Paturel [53] pointed out the necessary changes to be processed in hydrological regional norms in order to supply engineers with actual figures of rainfall and runoff characteristics, and new methods, able to account for the non-stationarity in hydrological variables.…”
Section: A Marked Increase In Runoff Coefficients and Discharges Of Smentioning
confidence: 99%
“…However, Roudier et al [42], conversely, considered that land use dynamics do not offset the effects of climate change on runoff in West Africa. At a broader scale, Mahé et al [26] recently proposed a synthesis of the hydrological behaviors observed throughout the whole Atlantic side of West Africa, ranging from the Maghreb to the Congo River mouths.…”
Section: Highlighting the Correlation Between Land Use/land Cover Andmentioning
confidence: 99%
See 2 more Smart Citations
“…10c), in contrast, the RRS captures well the low flows under 500 m 3 .s occur only 5% of time and more than 50% of times, the flow is close to zero. It is difficult to capture the daily discharge at this station, and 25 the large agricultural water demand over the Chelif basin (Mahe et al, 2013) probably contributes to the errors. But the main error source seems to be the forcing datasets, since the observations fall in their wide uncertainty range.…”
Section: Daily Timescalementioning
confidence: 99%